Actualidad de los centros Históricos. Una mirada local (2019)
This article is the producto of a reflection of the reality being experienced by our historic sites, especially the historical center of the city of TUnja, capital of the departamente on Boyacá. Under this perspective is a description of the process that led from the regulatory point of view regarding the regulation, protection and funding of historic centers, where they have adopted different policies that have generated consequences of varios kinds, the which are described in order to indentify the pros and cons of them, in this way to get to figure out viable and sustainable poposals from the economic point of view to finance projects in the historic center, and refer to the historical center as a large urban project GPU. The aim of thes papaer is to give the reader an overview on the issue raised and to call attention to the relevance of starting a reflection of the relationship between different aspects to consider achieving true sustainability of our town centers.